RESEPSI PEMBACA SASTRA ARAB DIGITAL: STUDI NOVEL AL-JINNU AL-'ĀSYIQ PADA APLIKASI WATTPAD - Fathan, Andini Adelia; Pilomonu, Nurkholis; Rohim, Fathur (Fakultas Adab dan Humaniora UIN Sunan Ampel Surabaya, 2026)
The development of digital literature through platforms such as Wattpad has transformed the interaction between text and readers, particularly through comment sections as spaces of immediate and participatory reception. This study aims to analyze readers’ reception of the Arabic digital novel Al-Jinnu al-ʿĀsyiq by Rofif using Stuart Hall’s encoding/decoding theory. Employing a qualitative descriptive-analytical approach, the data consist of selected reader comments collected from Wattpad and classified into three positions: dominant, negotiated, and oppositional readings. The findings reveal that dominant-hegemonic reading is the most prevalent, indicating that most readers interpret the narrative in alignment with the author’s intended meaning, as reflected in emotional engagement, empathy, and narrative appreciation. Negotiated readings also appear significantly, characterized by readers’ active interpretation through speculation, moral evaluation, and reconstruction of narrative possibilities, influenced by personal and cultural perspectives. In contrast, oppositional readings are limited and manifest as critical resistance toward narrative logic, characterization, or underlying values. These findings suggest that reader reception in digital Arabic literature is not merely an individual interpretive act but a socially mediated process occurring within interactive online spaces. Therefore, while Stuart Hall’s framework remains relevant, it requires further expansion to accommodate the collective, performative, and participatory nature of meaning-making in digital literary platforms.